2016
DOI: 10.3892/etm.2016.3970
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-302d downregulates TGFBR2 expression and promotes hepatocellular carcinoma growth and invasion

Abstract: Abstract. Hepatocellular carcinoma (HCC) is the second leading cause of cancer-associated mortality in China and the third leading cause worldwide. A number of microRNAs (miRNAs) have been implicated in cell cycle progression, growth, apoptosis, angiogenesis and metastasis in HCC. In the present study, reverse transcription-quantitative polymerase chain reaction analysis was used to detect the levels of miR-302d expression in the tissues of 30 patients with HCC. Cell cycle, growth, apoptosis and migration were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…miR-302d: Chen and colleagues demonstrated that the overexpression of miR-302d promoted cell growth and migration and suppressed apoptosis in HCC cell lines and that it promotes xenograft tumor growth in vivo . These mechanisms were found to be mediated by TGFbR2-signaling, a target of miR-302d[ 37 ].…”
Section: Mirnas In Hcc Molecular Pathwaysmentioning
confidence: 99%
“…miR-302d: Chen and colleagues demonstrated that the overexpression of miR-302d promoted cell growth and migration and suppressed apoptosis in HCC cell lines and that it promotes xenograft tumor growth in vivo . These mechanisms were found to be mediated by TGFbR2-signaling, a target of miR-302d[ 37 ].…”
Section: Mirnas In Hcc Molecular Pathwaysmentioning
confidence: 99%
“…Non-coding RNAs have been strongly implicated in the development course of GC 10 , 11 , 12 . Noncoding RNAs include small ncRNAs (<200nt) and long ncRNAs(>200nt).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs, which are a class of small ncRNAs, have been widely investigated for their capacity to regulate genes through causing mRNA degradation or repressing protein translation 13 . Numerous microRNAs have been implicated as potential oncogenes or tumor suppressors affecting cancer development 11 , 14 , 15 . Relative to other noncoding RNAs, long ncRNAs (lncRNAs) lack evolutionary conservatism among species 16 , and thus the mechanisms of lncRNAs in human diseases are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have causally linked individual microRNA expression changes to adverse biologic processes in HCC, including rapid proliferation, epithelial‐to‐mesenchymal transition (EMT), local tissue invasion, and vascular invasion . A summary of recently published studies with purported miRNA mechanisms is provided in Table . For the majority of cases, miRNA loss correlates to induction of a target oncogene, and miRNA gain correlates to repression of a target tumor suppressor.…”
Section: Microrna Hcc Subtypingmentioning
confidence: 99%